2018
DOI: 10.5194/wes-3-107-2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defects in composite wind turbine blades – Part 3: A framework for treating defects as uncertainty variables for blade analysis

Abstract: Abstract. Given that wind turbine blades are large structures, the use of low-cost composite manufacturing processes and materials has been necessary for the industry to be cost competitive. Since these manufacturing methods can lead to the inclusion of unwanted defects, potentially reducing blade life, the Blade Reliability Collaborative tasked the Montana State University Composites Group with assessing the effects of these defects. Utilizing the results of characterization and mechanical testing studies, pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Generally, manufacturing defects are formed in random locations and their formation is a random event. Riddle and colleagues [102] proposed probabilistic models to assess the reliability of a wind blade with known defects. Considering defects as random variables and design parameters in a parametric probabilistic analysis, the authors demonstrated that safety factors may be reduced, thanks also to a reduced uncertainty of the blade failure.…”
Section: Blade Failure Mechanisms and Role Of Manufacturing Defectsmentioning
confidence: 99%
“…Generally, manufacturing defects are formed in random locations and their formation is a random event. Riddle and colleagues [102] proposed probabilistic models to assess the reliability of a wind blade with known defects. Considering defects as random variables and design parameters in a parametric probabilistic analysis, the authors demonstrated that safety factors may be reduced, thanks also to a reduced uncertainty of the blade failure.…”
Section: Blade Failure Mechanisms and Role Of Manufacturing Defectsmentioning
confidence: 99%
“…In engineering applications, it is found that the delamination defects of UDL (unidirectional laminate) generated in manufacturing or transportation will reduce the strength of the spar cap. Material defects lead to premature failure of blades when subjected to the identified load in static tests or fatigue tests [6][7][8][9][10][11][12][13][14]. Some studies present that delamination and other defects caused by stress will significantly reduce the blade's global performance, especially the buckling at the trailing edge [15][16][17].…”
Section: Introductionmentioning
confidence: 99%